2017
DOI: 10.1186/s13024-017-0216-6
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 deficiency exacerbates tau pathology through dysregulated kinase signaling in a mouse model of tauopathy

Abstract: BackgroundGenetic variants of the Triggering Receptor Expressed on Myeloid Cells-2 (TREM2) confer increased risk of developing late-onset Alzheimer’s Disease (LOAD) and other neurodegenerative disorders. Recent studies provided insight into the multifaceted roles of TREM2 in regulating extracellular β-amyloid (Aβ) pathology, myeloid cell accumulation, and inflammation observed in AD, yet little is known regarding the role of TREM2 in regulating intracellular microtubule associated protein tau (MAPT; tau) patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
180
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(202 citation statements)
references
References 37 publications
(29 reference statements)
5
180
1
Order By: Relevance
“…Here, we show that variants within this AD risk locus modify CSF sTREM2 levels. Previous research has already suggested that changes in sTREM2 levels, or TREM2 biology in general, are likely involved in disease pathology (12)(13)(14)(15)(16)(17)(18)24). These MS4A variants also impact MS4A4A and MS4A6A expression in human blood and brain tissue, as previously reported (44,45).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Here, we show that variants within this AD risk locus modify CSF sTREM2 levels. Previous research has already suggested that changes in sTREM2 levels, or TREM2 biology in general, are likely involved in disease pathology (12)(13)(14)(15)(16)(17)(18)24). These MS4A variants also impact MS4A4A and MS4A6A expression in human blood and brain tissue, as previously reported (44,45).…”
Section: Discussionsupporting
confidence: 67%
“…On the other hand, a common phenotype across mouse models of amyloidosis is that reduction or loss of Trem2 leads to fewer amyloid plaque-associated microglia (9,14,16). Other studies indicate that Trem2 deficiency protects against neurodegeneration through a dampened microglial-response to tau pathology (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Pure Tauopathy models have also shown conflicting results when TREM2 was knocked out. TREM2 KO‐hTau mice were shown by one group to have increased pathology and neurodegeneration (Bemiller et al, ), while another group reported decreased neuroinflammation and decreased neurodegeneration in the PS19 Tau protein transgenic mouse model (Leyns et al, ). In a primary microglia–neuron co‐culture, Tau hyperphosphorylation was shown to result from LPS‐induced inflammation, suggesting that inflamed microglia can induce Tau pathology.…”
Section: Trem2mentioning
confidence: 99%
“…Pure Tauopathy models have also shown conflicting results when TREM2 was knocked out. TREM2 KO-hTau mice were shown by one group to have increased pathology and neurodegeneration (Bemiller et al, 2017), while another group reported decreased neuroinflammation and decreased neurodegeneration in the PS19…”
Section: Trem2 Loss-of-function Mutations Are Associated With Neuromentioning
confidence: 99%
“…A LOF mutation in the lipid sensing function, a minimotif activity of Trem2 deficient mice may be the underlying mechanism for the loss of microglia proliferation and microglial response to Aβ plaques or reduced infiltration of peripheral macrophages [251,252]. In addition, Trem2 deficiency leads to exacerbated aggregation of tau in a mouse model of tauopathy [253]. These findings demonstrate that TREM2 has complex multiple roles in regulating Aβ and tau pathologies that may reflect its distinct functions at different stages in AD pathology [254].…”
Section: Genetics and Epigenetics Of Minimotifs In Ndsmentioning
confidence: 86%